Analisis Perkembangan UMKM di Kecamatan Kota Kisaran Barat pada Masa Pandemi Covid-19 2020-2021 - Suci Pranasari; Zuhrinal M. Nawawi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the development of MSMEs in Kota Kisaran Barat District during the COVID-19 pandemic (2020-2021). The research method used is descriptive qualitative. This research method utilizes qualitative data and is described descriptively. This research method is often used to analyze events, phenomena, or social circumstances. The results of this study are the development of MSMEs in Kota Kisaran Barat District during the Covid-19 Pandemic (2020-2021). Keywords: Development, MSMEs, the pandemic period, covid-19